The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1007/s10725-005-5990-4
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Salt Stress on the Regulation of Maize (Zea mays L.) Genes Involved in Polyamine Biosynthesis

Abstract: A cDNA for spermidine synthase (SPDS), which converts putrescine to the higher polyamine spermidine using decarboxylated S-adenosylmethionine as a cofactor, was isolated from Zea mays leaves (Zmspds2A). Comparison of the deduced amino acid sequence revealed a high homology (81.9%) with Oryza sativa SPDS2. RT-PCR analyses showed that Zmspds2A was equally expressed in leaves, stem and roots. In contrast, transcripts of other genes related to polyamine biosynthesis (Zmodc, adc and samdc) showed tissue-specific re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
31
0
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(36 citation statements)
references
References 41 publications
3
31
0
2
Order By: Relevance
“…Rodríguez-Kessler et al (2006) reported the upregulation of two genes, Zmodc and Zmspds2A, responsible for polyamine and spermidine synthesis under salt stress in maize. Genotypic differences in the relative concentration of six β-expansin transcripts together with differences in the abundance of β-expansin protein were observed in response to NaCl stress.…”
Section: Molecular Mechanismsmentioning
confidence: 99%
“…Rodríguez-Kessler et al (2006) reported the upregulation of two genes, Zmodc and Zmspds2A, responsible for polyamine and spermidine synthesis under salt stress in maize. Genotypic differences in the relative concentration of six β-expansin transcripts together with differences in the abundance of β-expansin protein were observed in response to NaCl stress.…”
Section: Molecular Mechanismsmentioning
confidence: 99%
“…This indicated that the genes were disparately regulated during stress, a phenomenon which could be dependent upon several factors, such as plant species, duration, and intensity of stress and stress sensitivity of the experimental materials (Chattopadhyay et al 1997;Li and Chen 2000a;Hao et al 2005a, b;Liu et al 2006b). In spite of the existence of several polyamine biosynthetic enzymes, the global expressions of a whole set of the genes in response to stress has only been analyzed in a few cases (Urano et al 2003;Rodríguez-Kessler et al 2006;Alcázar et al 2006a;Liu et al unpublished data). It remains unclear why the genes in the polyamine biosynthetic gene family responded differently in response to stress.…”
Section: Cloning and Expression Of Polyamine Biosynthetic Genes Undermentioning
confidence: 99%
“…Because of their fully protonated and polycationic nature at physiological pH, PAs can bind strongly to negatively charged cellular components such as nucleic acids, proteins and phospholipids . PAs are biologically active compounds involved in various physiological processes, and numerous studies reported that PAs can improve plant resistance to various abiotic stresses (Alcazar et al 2010;Rodríguez-Kessler et al 2006). Several mechanisms for the protective nature of PAs have been postulated, including stabilizing the function of chromosomes (Kasinathan and Wingler 2004), retarding lipid peroxidation and preserving membrane integrity (Ha et al 1998).…”
Section: Introductionmentioning
confidence: 99%